School counseling practicum and internship 30 essential lessons - Hamlet, Helen S. (SAGE, 2017)
School Counseling Practicum and Internship: 30 Essential Lessons combines crucial counselor knowledge with the experience of experts in the field into one practical guide for addressing the real world of school counseling. Drawing on more than a decade of teaching, author Helen S. Hamlet, PhD presents a collection of lessons and techniques that includes forms, websites, activities, and current information focusing on a range of challenging issues. This unique text is a resource that practicum and internship students, counselor educators, and practicing school counselors will keep and refer to for years to come. -- Provided by publisher